REPRESENTASI MAKNA SUNYI DAN PEMBENTUKAN IDENTITAS TOKOH RARA DALAM NOVEL SUNYI ADALAH MINUMAN KERAS KARYA SAPARDI DJOKO DAMONO: KAJIAN SEMIOTIKA CHARLES SANDERS PEIRCE - Basir, Nur Putri Indah Sari; Andi Karman; Aslan Abidin; Usman (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to uncover the representation of the meaning of the word "sunyi" (silence/solitude) in the novel Sunyi adalah Minuman Keras (Silence is a Strong Drink) by Sapardi Djoko Damono, and its connection to the formation of the identity of the main character, Rara, amid modern life and digital spaces. The study employs a descriptive qualitative approach with semiotic analysis based on Charles Sanders Peirce's framework, encompassing icon, index, and symbol. The research data consist of narrative excerpts, dialogues, phrases, and character actions that represent silence, collected through reading and note-taking techniques, then analyzed interpretively. The findings reveal that silence is represented iconically through private spaces, objects, and disrupted communication; indexically as the impact of family trauma, social norm pressures, and interpersonal communication failures; and symbolically as a metaphor for alienation, escapism, as well as a space for reflection in the identity-seeking process of modern humans. Silence in the novel is not passive in nature; rather, it plays an active role in shaping the inner experience and the dynamic, ever-evolving identity of the main character. This study affirms that silence functions as a meaning construction that reflects the identity crisis and human relationships in the digital era.